Nor sure what you're doing on the bottom but use point slope thing
y-0=-2(x+2)
y=-2x+2
So not sure what you're asking but...
yeah, you're right.
3<em>x</em> ² - 2<em>x</em> + 1 = 2<em>x</em> ² - 3<em>x</em> + 7
<em>x</em> ² + <em>x</em> - 6 = 0
(<em>x</em> + 3) (<em>x</em> - 2) = 0
<em>x</em> + 3 = 0 <u>or</u> <em>x</em> - 2 = 0
<em>x</em> = -3 <u>or</u> <em>x</em> = 2
Answer:
Step-by-step explanation:
1. Draw a line down the middle of the equal sign .
2.Divide 4x/4. Which equals x.
3. Divide 6/4. Which equals 1 and 2/4 or 1 and 1/2.
4. X=1 2/4
5. Check=
Y=4x+6
Plug 4 with 1 2/4. Which equals 6.
6+6=12
X=1 2/4 Y=12
Answer:
1/3
Step-by-step explanation:
Answer:
Y =1 is a good answer for this question.